The formation of ZnO structures using thermal oxidation: How a previous chemical etching favors either needle-like or cross-linked structures. (15th March 2020) - Rojas-Chávez, H.; Cruz-Martínez, H.; Montejo-Alvaro, F.; Farías, Rurik; Hernández-Rodríguez, Y.M.; Guillen-Cervantes, A.; Ávila-García, A.; Cayetano-Castro, N.; Medina, D.I.; Cigarroa-Mayorga, O.E.
Abstract: Thermal oxidation of Zn polycrystalline elemental foils –previously etched at different chemical conditions– was used to study the formation of ZnO structures. Two distinct etching solutions were used: 0.5 M HNO3 and 11 M HNO3 . Based on field emission scanning electron microscopy results, by modifying the etching conditions, the ZnO structures were different regarding morphology: needle-like ZnO microstructure arrays were formed when Zn foil was chemically etched using the 0.5 M HNO3 solution, whilst a cross-linked morphology was obtained when the etching solution changed to 11 M HNO3 concentration. However, the elemental mapping showed identical chemical composition of both kinds of ZnO microstructures. The focused ion beam-transmission electron microscopy specimens revealed the occurrence of ZnO nanostructures, in both kinds of as-oxidized samples, obtained after 2 h of thermal oxidation at 400 °C. Finally, both needle- and cross-linked microstructures were evaluated in terms of their optical properties. According to the experimental findings, it was found that these structures can be applied in optoelectronic devices working around the green range of the visible electromagnetic spectrum, exhibiting the cross-linked sample the highest radiation intensity.